The short-, medium-, and long-term prevalence of physical health comorbidities in first-episode psychosis: a systematic review and meta-analysis protocol [version 2; peer review: 3 approved] - Michael Norton; Brian O'Donoghue; Mary Clarke; Karen O'Connor; Jennifer Murphy; Anna Zierotin (HRB Open Research)
Background Individuals with first-episode psychosis (FEP) face an increased risk of physical comorbidities, notably cardiovascular diseases, metabolic disorders, respiratory disorders, and certain types of cancer. Previous reviews report pooled physical health prevalence from chronic psychosis and FEP groups. By contrast, this review will focus on antipsychotic-naïve FEP cohorts and incorporate data from observational longitudinal studies and antipsychotic intervention studies to understand the progression of physical health comorbidities from the onset to later stages of psychosis. This review aims to examine the short-, medium-, and long-term period prevalence of these comorbidities in FEP and variations related to demographic factors. Methods Using the PRISMA and MOOSE guidelines, Medline, Embase, PsycINFO, and CINAHL+, as well as Clinical Trials gov.uk, OpenGrey, WHO International Clinical Trials Registry Platform, Current Controlled Trials, United States National Institute of Health Trials Registry, and the Irish Health Repository, will be searched from inception. Longitudinal studies and antipsychotic intervention studies monitoring health outcomes in antipsychotic naïve FEP individuals will be eligible for inclusion. Two reviewers will independently screen titles, abstracts, and full-text articles. Risk of bias will be assessed using the Joanna Briggs Institute Critical Appraisal Checklist. A meta-analysis of the short-, medium-, and long-term prevalence of cardiovascular, metabolic, cancer, and respiratory outcomes and a narrative synthesis will be conducted. Where feasible, a meta-regression on the impact of demographic variables will be conducted. Potential limitations include the risk of diagnostic heterogeneity across studies and possible underreporting of certain comorbidities. Conclusions This systematic review will clarify the progression of physical health comorbidities in FEP, informing early intervention strategies and policies. Subsequent findings will be submitted to a leading journal, supplemented by a recovery education module and a lay summary for wider dissemination. Registration The study was registered in PROSPERO, the International Prospective Register of Systematic Reviews (CRD42023431072; 17/06/2023).